Factors Influencing The Use of E-Wallets In Paying BPJS Contributions (Case Study of The Sialang Village Community) - Nur Aprillia; Tri Inda Fadhila Rahma; Atika Atika (Dinasti Publisher, 2024)
This research aims to find out and analyze what factors influence the use of E-wallet in paying BPJS contributions. The research method used is quantitative descriptive. The population in this research is the people of Sialang Village. This research used a purposive sampling technique with a sample size of 100 people. In this research, data analysis uses normality test, linear regression test, partial test, simultaneous test , coefficient of determination test using the SPSS 25 program. Partial research results show that literacy and security have no influence on usage decisions, price and service have a significant and significant influence on decisions. use. Meanwhile, simultaneously, literacy, security, price and service influence usage decisions. Based on the results of testing the coefficient of determination, the Adjusted R Square value was obtained, namely 0.630 or 6.30 % . This means that the decision to use is 6.30 % . Meanwhile , 4.70 % is influenced by other factors not included in the regression model.